2020
DOI: 10.14720/aas.2020.115.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of amaranth species (Amaranthus spp.) in the temperate continental climate of Russian Federation

Abstract: Comparative study of amaranth species (Amaranthus spp.) in the temperate continental climate of Russian FederationAbstract: Field experiments were carried out in the Chuvash Republic, which is located in the center of the European part of Russia on the banks of the Volga River and has a moderately continental climate with warm summers, cold winters, well-defined transitional seasons and average annual rainfall of 500 mm. There are many cultural and wild species of amaranth in nature, differing in morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Regarding cultivar selection, growers must take into consideration the climate conditions of the region in which grain amaranth will be cultivated. Under temperate climate conditions, given that grain amaranth has a higher demand for heat than moisture, cultivars with a fast development and short growth cycle are preferred in order to avoid being damaged by early frosts (Dmitrieva & Ivanov, 2020). The Amaranthus cruentus BRS Alegria cultivar was developed by the Brazilian Agricultural Research Corporation (Embrapa) and is reported to have achieved, in a 90-day crop cycle, a grain yield of up to 2.3 t ha −1 and up to 5.6 t ha −1 of total dry biomass (Ferreira et al, 2014).…”
mentioning
confidence: 99%
“…Regarding cultivar selection, growers must take into consideration the climate conditions of the region in which grain amaranth will be cultivated. Under temperate climate conditions, given that grain amaranth has a higher demand for heat than moisture, cultivars with a fast development and short growth cycle are preferred in order to avoid being damaged by early frosts (Dmitrieva & Ivanov, 2020). The Amaranthus cruentus BRS Alegria cultivar was developed by the Brazilian Agricultural Research Corporation (Embrapa) and is reported to have achieved, in a 90-day crop cycle, a grain yield of up to 2.3 t ha −1 and up to 5.6 t ha −1 of total dry biomass (Ferreira et al, 2014).…”
mentioning
confidence: 99%